The effect of the application of different levels of movement variability on movement outcome - Tucker, C. B.; Anderson, R.; Kenny, I. C. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
The aim of this study was to assess the effect of the application of a previously validated golfer computer model on different levels of movement variability relative to a shot outcome measure: club head velocity. Movement variability was applied to the computer model on six measures sequentially throughout the body of the computer model. Four different levels of variability, 25%, 50%, 75% and 100% variability, were applied to x, y and z positional data of the aforementioned measures. Simulations were then performed with ADAMS/LifeMOD software for each level of movement variability applied to the measures in question. Club head velocity was measured during the simulation. The results suggest that movement variability application at these landmarks does not have an effect on outcome. These results potentially have implications for the coaching of the participant.